Economic Thought of Ibn Taimiyah and Relevance to the World Economic and Community Economic System - Ahmad Maulidizen (UIN Sunan Kalijaga Yogyakarta, 2019)
This article describes the biography and economic thinking of Ibn Taimiyah, a great Muslim thinker in 1263 M / 661 H - 1328 M / 728 H. This research is a research library with a descriptive approach. And explain the analysis of the Economic Thought of Ibn Taimiyah and Relevance to The World Economic and Community System. Data collection methods in this study using documentation, then analyzed using inductive, deductive and comparative methods. His contributions and thoughts regarding (1) buying and selling transactions include fair prices, market mechanisms, and price regulation, (2) Money and monetary policy, including the characteristics and functions of money, decreasing currency values, and a bad currency will get rid of the currency the good one. Ibn Taimiyyah has a framework that is in line with the opinion that states that the Islamic economy, both its system and its law, is an integral part of the world economic system and society.[Artikel ini menjelaskan tentang biograpi dan pemikiran ekonomi Ibn Taimiyah, seorang pemikir Muslim besar Tahun 1263 M/661 H – 1328 M/728 H. This research is a library research with descriptive approach. That is to describe or explain the analysis of Economic Thought of Ibn Taimiyah and Relevance with The World Economic and Community System. Data collection methods in this study using documentation, then analyzed using inductive, deductive and comparative methods. Sumbangan dan pemikirannya mengenai (1) transaksi jual beli meliputi harga yang adil, mekanisme pasar, dan regulasi harga, (2) Uang dan kebijakan moneter, meliputi karakteristik dan fungsi uang, penurunan nilai mata uang, dan Mata uang yang buruk akan menyingkirkan mata uang yang baik. Ibn Taimiyyah mempunyai kerangka pikir yang sejalan dalam pendapat yang menyatakan bahwa ekonomi syariah, baik sistem maupun hukumnya, merupakan bagian tak terpisahkan dari sistem pemerintahan dan ketatanegaran.]